NANOINDENTATION AND ACCELERATED PROPERTY MAPPING OF PORTLAND CEMENT PASTE - Jiří Němeček; Jiří Němeček; Jaroslav Lukeš (Acta Polytechnica CTU Proceedings, 2020)
This paper presents a new nanoindentation mode: accelerated property mapping (XPM) applied to one year old Portland cement paste. The principle of the innovative method is similar to classical quasi-static nanoindentation but the time necessary for performing one indent is significantly decreased from minutes to tenths of seconds. The XPM mode is capable of measuring maps of local mechanical properties (reduced modulus, hardness). The method was compared to classical nanoindentation mode. The main advantages of XPM measurement are higher spatial resolution, lower property fluctuation and lower acquisition time. However, XPM is not able to measure some parameters such as creep. Also, high speed loading of XPM brings high strain effect which artificially shifts values of reduced modulus to higher values compared to quasi-static loading cases.